Carbon dot composites for bioapplications: a review. Issue 6 (21st January 2022) - Wu, Jiajia; Chen, Gonglin; Jia, Yinnong; Ji, Chunyu; Wang, Yuting; Zhou, Yiqun; Leblanc, Roger M.; Peng, Zhili
Abstract : Recent advancements in the synthesis of carbon dot composites and their applications in biomedical fields (bioimaging, drug delivery and biosensing) have been carefully summarized. The current challenges and future trends of CD composites in this field have also been discussed. Abstract : Carbon dots (CDs) have received extensive attention in the last decade for their excellent optical, chemical and biological properties. In recent years, CD composites have also received significant attention due to their ability to improve the intrinsic properties and expand the application scope of CDs. In this article, the synthesis processes of four types of CD composites (metal–CD, nonmetallic inorganics–CD, and organics–CD as well as multi-components—CD composites) are systematically summarized first. Then the recent advancements in the bioapplications (bioimaging, drug delivery and biosensing) of these composites are also highlighted and discussed. Last, the current challenges and future trends of CD composites in biomedical fields are discussed.